Inai Cultural Dialectics: Indigenous Knowledge of Natural Dyes among the Iban Dayak as a Response to the Phenomenon of Fast Fashion - Darmawan, Diaz Restu; Novianti, Nadia; Praptantya, Donatianus BSE. (Institut Seni Indonesia Denpasar, 2024)
Basic human needs, including clothing, have become commodities in the hands of industrial players, leading to a culture of consumption and negatively impacting the environment. The fast fashion industry presents numerous challenges requiring human-based solutions to reduce ecological damage. One solution is reintroducing past clothing practices and prioritizing environmentally friendly materials and techniques. Using natural materials with minimal environmental impact in clothing production is becoming more popular. One ecologically friendly material is natural dye, a traditional practice of the Dayak Iban community in Kapuas Hulu Regency, West Kalimantan. This article employs qualitative methods and literature studies to describe the natural dyeing process in the Dayak Iban community, emphasizing the continuation of tradition. The experience of researchers who have lived with indigenous communities in Menua Sadap village can provide valuable objective observation and interview data. In the Dayak Iban tradition, the makers of naturally dyed cloth are predominantly adult women, referred to as Inai. This article describes the local knowledge of the Inai regarding natural dyeing and how this process can solve the environmental damage caused by fast fashion. The indigenous peoples are highly concerned about their climate and environmental conditions as their livelihoods depend on the natural resources where they live. This was then strengthened by customary law so that environmental damage in Menua Sadap occurred less quickly than in urban areas, which often happens.